Evaluation and Optimization of Outdoor Thermal Comfort of Block-Style Commercial Complex in Hot Summer and Cold Winter Regions of China - Yeheng Zhou; Jiang Zhu; Eryu Ni; Yanzhe Hu (Buildings)
In recent years, block-style commercial complexes have become a prominent form of commercial architecture in many Chinese cities. The thermal comfort of their outdoor spaces significantly influences people’s activities and the overall quality of these areas. This study explores the relationship between the morphological elements of outdoor spaces in such complexes and thermal comfort, using quantifiable methods to identify key control indicators. Enhancing thermal comfort is crucial for improving spatial quality, increasing dwell time, and boosting commercial vibrancy. Focusing on the hot summer and cold winter climate of Shanghai, this research analyzed two representative block-style commercial complexes. It employed computer simulations and sensory comfort surveys to demonstrate that block morphology significantly impacts outdoor thermal comfort. Three control variables—street density, number of street intersections, and street orientation—were selected to study their effects. Spatial prototypes were categorized, and their thermal comfort performance was evaluated using numerical simulations. Based on these findings, spatial morphology was iteratively optimized. This study concluded by proposing evaluation indicators for spatial morphology control elements to enhance outdoor thermal comfort. It also provided external spatial layout strategies for block-style commercial complexes in similar climates, offering architects and urban designers decision-making criteria to improve thermal comfort in outdoor spaces. This research contributes to creating more comfortable and vibrant urban environments.